Intersubband transitions in InAs/GaSb superlattices in a parallel magnetic field - De Meester, R; Peeters, F; Lakrimi, M; Nicholas, R; Poulter, A; Mason, N; Walker, P (Elsevier, 2000)
We present a theoretical study of intersubband transitions (IST) in InAs/GaSb superlattices in the presence of a parallel magnetic field. Starting from a model describing a single electron in a single quantum well and extending it to include many-body effects and the non-parabolicity of the InAs conduction band we are able to explain the recent cyclotron resonance experiments on narrow and wide InAs/GaSb quantum wells.